RACK1 and β-arrestin2 attenuate dimerization of PDE4 cAMP phosphodiesterase PDE4D5 - Bolger, Graeme B. (Cell Signal, 2015)
PDE4 family cAMP-selective cyclic nucleotide phosphodiesterases are important in the regulation of cAMP abundance in numerous systems, and thereby play an important role in the regulation of PKA and EPAC activity and the phosphorylation of CREB. We have used the yeast 2-hybrid system to demonstrate recently that long PDE4 isoforms form homodimers, consistent with data obtained recently by structural studies. The long PDE4 isoform PDE4D5 interacts selectively with β-arrestin2, implicated in the regulation of G-protein-coupled receptors and other cell signalling components, and also with the β-propeller protein RACK1. In the present study, we use 2-hybrid approaches to demonstrate that RACK1 and β-arrestin2 inhibit the dimerization of PDE4D5. We also show that serine-to-alanine mutations at PKA and ERK1/2 phosphorylation sites on PDE4D5 detectably ablate dimerization. Conversely, phospho-mimic serine-to-aspartate mutations at the MK2 and oxidative stress kinase sites ablate dimerization. Analysis of PDE4D5 that is locked into the dimeric configuration by the formation of a trans disulfide bond between Ser261 and Ser602 shows that RACK1 interacts strongly with both the monomeric and dimeric forms, but that β-arrestin2 interacts exclusively with the monomeric form. This is consistent with the concept that β-arrestin2 can preferentially recruit the monomeric, or “open,” form of PDE4D5 to β(2)-adrenergic receptors, where it can regulate cAMP signalling.